Platform Practices in the Cultural Industries: Creativity, Labor, and Citizenship. (November 2019) - Duffy, Brooke Erin; Poell, Thomas; Nieborg, David B.
The rise of contemporary platforms—from GAFAM in the West to the "three kingdoms" of the Chinese Internet—is reconfiguring the production, distribution, and monetization of cultural content in staggering and complex ways. Given the nature and extent of these transformations, how can we systematically examine the platformization of cultural production? In this introduction, we propose that a comprehensive understanding of this process is as much institutional (markets, governance, and infrastructures), as it is rooted in everyday cultural practices. It is in this vein that we present fourteen original articles that reveal how platformization involves key shifts in practices of labor, creativity, and citizenship . Diverse in their methodological approaches and topical foci, these contributions allow us to see how platformization is unfolding across cultural, geographic, and sectoral-industrial contexts. Despite their breadth and scope, these articles can be mapped along four thematic clusters: continuity and change; diversity and creativity; labor in an age of algorithmic systems; and power, autonomy, and citizenship.